Monetary policy under imperfect information and consumer confidence - Jan-Niklas Brenneisen (Kiel University, Department of Economics, 2020)
Although it is generally accepted that consumer confidence measures are informative signals about the state of the economy, theoretical macroeconomic models designed for the analysis of monetary policy typically do not provide a role for them. I develop a framework with asymmetric information in which the efficacy of monetary policy can be improved, when the imperfectly informed central banks include confidence measures in their information set. The beneficial welfare effects are quantitatively substantial in both a stylized New Keynesian model with optimal monetary policy and an estimated medium-scale DSGE model.
Keywords: D82; D83; D84; E52; E58; E71; 330; Consumer confidence; Monetary policy; Asymmetric information; Imperfect Information; New Keynesian macroeconomics; DSGE models